Utilizing Go-Yoga Smartphone Application to Prevent Preeclampsia in Pregnant Women - Zakaria, Rabia; Astuti, Siti Choirul Dwi (JURNAL INFO KESEHATAN, 2022)
After bleeding, hypertension is the second leading cause of maternal death.  Hypertension is caused by a combination of factors, including increased stress and a low level of albumin. All of these changes will cause complications and necessitate long-term medication therapy. As a result, complementary therapies such as family roles and yoga are required. Many people are unfamiliar with yoga movements, so this study provides innovation by incorporating yoga into a smartphone application. The objective of the study is to determine the differences in the implementation of the Go-Yoga smartphone application and the role of the family in pregnant women in the III trimester on blood pressure and albumin levels. This type of research is quasi-experimental involving 60 pregnant women in the third trimester. In Group I, 20 pregnant women practiced yoga with books; in Group II, 20 pregnant women exercised yoga with the Go-Yoga app without their families; and in Group III, 20 pregnant women practiced yoga with their families. The study's results revealed significant blood pressure, with the third group having the highest average (p = 0.000 1). Pregnant women who utilize the Go-Yoga app with their families have lower blood pressure than other groups. Furthermore, pregnant women who employ the Go-Yoga app with their families have higher albumin levels than other groups. Therefore, this study suggests employing the Go-Yoga application with the family prevents hypertension in pregnancy.